A new method for measurement and calculation of unit width suspended sediment transport rate. Issue 3 (16th February 2023) - Zheng, Haolei; Sun, Zhilin; Zheng, Rong; Sun, Lixia
Abstract: The unit width suspended sediment transport rate is the basis for calculating river sediment flux, which provides an important measure of river hydrology and morpho-dynamics. By integrating the vertical distribution of the suspended sediment concentration and logarithmic flow velocity, the formula for unit width suspended sediment transport rate is presented. Based on this formula, the calculation of the near-bed relative transport rate missing in field measurement is given. Moreover, a new stratified water sampling device is invented for suspended sediment transport rate measurement by the six-point method at Mengsheng hydrological station in the Lancang River basin. Results of 24 sets of measurements show that the near-bed relative sediment transport rate ranges from 3.4 to 10.7% and is significantly positively correlated with the suspension index. The unit width suspended sediment transport rate measured by the traditional depth integrating method is on average 15.0% smaller than that calculated by the theoretical formula, which can be a reference for correcting the sediment transport rate based on the traditional method. This work provides a new device and a new method for the measurement and calculation of the unit width transport rate of suspended sediment, which has theoretical and practical significance. HIGHLIGHTS: A new formula of unit width suspended sediment transport rate is established. Theoretically defined and analyzed the near-bed relative sediment transport rate. A stratified sampling device based on the vacuum principle was invented and applied. A comparison test of the sediment transport rate was carried out at Mengsheng station. The results provide a reference for the correction of the sediment transport rate. Graphical Abstract